2008
DOI: 10.1016/j.ejheart.2008.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Depression worsens outcomes in elderly patients with heart failure: An analysis of 48,117 patients in a community setting

Abstract: Aims: To assess the relationship between depression and clinical outcomes among elderly patients with heart failure (HF) in a community setting. Methods and results: To identify patients with HF and depression we used record linkage analysis of hospital discharge records, prescription databases and vital statistics. All consecutive patients aged ≥ 60 years in 6 Local Health Authorities in Italy were included. HF was defined as either: 1) hospital discharge with HF diagnosis (ICD-9: 428) and/or 2) chronic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…In the present study, 7.2% of the heart failure patients received an antidepressant. Similar results were found in a large community cohort of elderly patients with SHF [10]. In other studies, it has been found that 28 to 48% of SHF patients in an out-patient clinic experience depression when depression is defined by the questionnaire [11,12].…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, 7.2% of the heart failure patients received an antidepressant. Similar results were found in a large community cohort of elderly patients with SHF [10]. In other studies, it has been found that 28 to 48% of SHF patients in an out-patient clinic experience depression when depression is defined by the questionnaire [11,12].…”
Section: Discussionsupporting
confidence: 81%
“…PS methodology is a useful tool to reduce selection bias in observational studies 15,16 and has already been used in many therapeutic fields. [33][34][35][36] Treatment comparisons in such contexts are still prone to residual bias, which PS methods cannot take into account, however; and although sensitivity analysis can overcome residual bias by addressing its extent, these attempts to assess treatment effectiveness should be considered exploratory in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Depression increased all-cause mortality by 20% in elderly patients with HF; 49 anxiety disorders are present in up to 40% of PD patients, substantially adversely affecting quality of life. 50 Mood disorders are frequently underrecognized and undertreated in these populations, due in part to lack of adequate assessment tools, differences in presentations of mood disorders in these populations, and a failure of primary treating physicians to evaluate psychiatric issues.…”
Section: B) Depression Anxiety and Griefmentioning
confidence: 99%
“…Changes in aging physiology may alter perception, characteristic, and intensity of nonpain symptoms. 49 Understanding the relationship between aging physiology and symptom perception will inform effective symptom assessment and treatment.…”
Section: Outline Of Knowledge Gaps A) Pathophysiologymentioning
confidence: 99%